Phillipsins A and B from Zingiber phillippsii Mood & Theilade in Borneo - Takashi Kamada; Julius Kulip; Kazuki Tani; Chin-Soon Phan; Kishio Hatai; Charles Santhanaraju Vairappan (2018)
Two new aromatic compounds, phillipsins A (1) and B (2) were isolated from the Bornean wild ginger Zingiber phillippsii Mood & Theilade, and were characterized based on spectroscopic data (HRESI-MS, FTIR as well as 1D and 2D NMR). These metabolites also exhibited strong antifungal activity against selected fungi.